Calidad de vida relacionada con la salud en personal de enfermería que se encuentra en primera línea de atención a pacientes con sars-cov-2 covid-19 en el ámbito hospitalario: una revisión de literatura (2021)
Introduction: The behavior of the current SARS-CoV-2 COVID-19 pandemic, given its characteristics of spread, severity and lethality, added to the social, labor and health systems conditions, put at risk the different dimensions of the The health of the personnel in the first line of care, as well as its determinants, need to be recognized in order to prevent and deal with possible damage. Objective: To describe the current health situation with a focus on the quality of life and health of the nursing personnel who are in the first line of care for patients with SARS-CoV-2 COVID-19, reported in the literature. Methodology: A documentary review was carried out where the electronic resources PubMed, ScienceDirect, Scielo and Academic Google and official Web pages (WHO, PAHO, Ministry of Health and Social Protection, District Health Secretariat of Bogotá) are consulted. Results: The review carried out, include include 38 articles, which allowed identifying situations related to working conditions of increased working time, job insecurity, insufficient resources for care, including personal protection elements, such as those factors that provide more information on health of the nursing staff. Conclusions: As factors that most affect the quality of life of the nursing staff, those related to working conditions, discrimination and social stigma were identified. The dimensions of quality of life most affected in the framework of the pandemic are emotional health and mental health.